2017
DOI: 10.15626/eco-tech.2014.013
|View full text |Cite
|
Sign up to set email alerts
|

A study on methane degradation layer extracted from landfill mining

Abstract: Due to the harmful effect on the environment, landfill gas has to be collected and processed. One possible solution would be covering the landfill with a bioactive layer, where methane gas is oxidized.The aim of this research is to study the possibilities of extracting material for the methane degradation layer from the landfill itself by means of Landfill Mining (LFM). Chemical and biological properties as well as hydrophysical properties like hydraulic conductivity and saturated volumetric water content of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The high C/N ratio (Table 1) shows that the organic carbon had not fully mineralized in the landfill. Chemical and hydrological tests performed in a previous study [74] showed the optimal composition of the biocover for methane degradation as consisting of 60% fine fraction from landfill mining, 20% natural soil, and 20% mature sewage sludge compost. The objective of such adjustments was to reduce biological activity by adding mineral soil with a low microbial content and to increase the content of stabilized organic carbon by adding mature sludge compost.…”
Section: Unit Fine Fraction (Ff)mentioning
confidence: 92%
See 1 more Smart Citation
“…The high C/N ratio (Table 1) shows that the organic carbon had not fully mineralized in the landfill. Chemical and hydrological tests performed in a previous study [74] showed the optimal composition of the biocover for methane degradation as consisting of 60% fine fraction from landfill mining, 20% natural soil, and 20% mature sewage sludge compost. The objective of such adjustments was to reduce biological activity by adding mineral soil with a low microbial content and to increase the content of stabilized organic carbon by adding mature sludge compost.…”
Section: Unit Fine Fraction (Ff)mentioning
confidence: 92%
“…For instance, the heavy metal content in the FF had to meet the limit value for contaminated soil [73], even if it was excavated and backfilled at the same location, and even if it did not affect the functionality of the methane degradation layer. The actual characteristics of the biocover (Table 1) represent the outcome of adjusting the composition of the biocover material according to Pehme et al [74]. Table 1.…”
Section: Design Of a Biocovermentioning
confidence: 99%
“…Given the low levels of pollutants, the fine fraction could be used as future cover material for landfills. In the current project, the fine fraction was used as a methane degradation layer (Heinsoo et al, 2016;Pehme et al, 2014).…”
Section: Composition Of Fine Fraction (<40 Mm)mentioning
confidence: 99%
“…The local regulation required the waste capping with a 1.5 m thick layer of secondary material derived from a fine fraction of waste. The cover material was obtained from approximately 80,000 m 3 of waste after careful sorting and sieving by specific techniques, adding matured compost and regular soil [48][49][50][51][52].…”
Section: Kudjape Landfill: Serving Society and Sciencementioning
confidence: 99%
“…At best, dumps are intended to be revitalized for the purpose of surrounding environmental improvement, adding societal value to degraded areas and maintaining public health [8,[13][14][15][16]. Added value can be increased by material and energy recovery but, generally, only a small part of old or closed landfills and dumps deals with modern recycling and waste logistics centres nowadays [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%